2004
DOI: 10.1111/j.1432-1033.2004.04299.x
|View full text |Cite
|
Sign up to set email alerts
|

Injection of poly(β‐l‐malate) into the plasmodium of Physarum polycephalum shortens the cell cycle and increases the growth rate

Abstract: Poly(b-L-malate) (PMLA) has been reported as an unconventional, physiologically important biopolymer in plasmodia of myxomycetes, and has been proposed to function in the storage and transport of nuclear proteins by mimicking the phospho(deoxy)ribose backbone of nucleic acids. It is distributed in the cytoplasm and especially in the nuclei of these giant, multinucleate cells. We report here for the first time an increase in growth rate and a shortening of the cell cycle after the injection of purified PMLA. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The plasmodium, used in this study, is a giant and multinucleated cell with a veined structure and no internal cell walls. So far, Physarum has been used mainly in studies on the cell cycle, inheritance of mitochondrial DNA, and cytoplasmic streaming [13–18]. Physarum is also an appropriate model organism for studies on responses to environmental stress.…”
mentioning
confidence: 99%
“…The plasmodium, used in this study, is a giant and multinucleated cell with a veined structure and no internal cell walls. So far, Physarum has been used mainly in studies on the cell cycle, inheritance of mitochondrial DNA, and cytoplasmic streaming [13–18]. Physarum is also an appropriate model organism for studies on responses to environmental stress.…”
mentioning
confidence: 99%
“…The microplasmodial culture appeared light yellow. It has been reported that for many strains of P. polycephalum , the color of microplasmodia is mostly yellow, such as M 3 CVII and M 3 CVIII, except for two albino strains, including LU897 × LU898 and LU887, which have a white color . The microplasmodia were of different sizes, ranging from 50 to 2,000 μm in diameter.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that for many strains of P. polycephalum, the color of microplasmodia is mostly yellow, such as M 3 CVII and M 3 CVIII, except for two albino strains, including LU897 × LU898 and LU887, which have a white color. 15 The microplasmodia were of different sizes, ranging from 50 to 2,000 μm in diameter. The resulting sizes were somewhat larger than reported in previous studies, in which microplasmodial size varied from 50 to 1,000 μm.…”
Section: Discussionmentioning
confidence: 99%
“…The other tube was kept on ice and was used to measure the amount of endogenous malate. Polymalic acid was assessed on basis of the malate dehydrogenase reaction as described [8]. Protein was assayed according to the method of Bradford [38].…”
Section: Methodsmentioning
confidence: 99%
“…Due to its structural similarity to the backbone of nucleic acids, PMLA has been proposed to bind nuclear proteins and function in a molecular transporter system ([6] and references therein). Injection of PMLA into plasmodia increased the growth rate and shortened cell cycle duration, indicating that it could also be involved in the molecular events responsible for the synchronization of events in the plasmodium [7,8]. PMLA is synthesized from l ‐malate derived from d ‐glucose through the glycolytic pathway and the tricarboxylic acid cycle [9].…”
mentioning
confidence: 99%